Complement-Coagulation Cross-Talk: A Potential Mediator of the Physiological Activation of Complement by Low pH - Kenawy, Hany Ibrahim; Boral, Ismet; Bevington, Alan (Frontiers in Immunology, 2015)
The complement system is a major constituent of the innate immune system. It not only bridges innate and adaptive arms of the immune system but also links the immune system with the coagulation system. Current understanding of the role of complement has extended far beyond fighting of infections, and now encompasses maintenance of homeostasis, tissue regeneration and pathophysiology of multiple diseases. It has been known for many years that complement activation is strongly pH sensitive, but only relatively recently has the physiological significance of this been appreciated. Most complement assays are carried out at the physiological pH 7.4. However, pH in some extracellular compartments, for example renal tubular fluid in parts of the tubule, and extracellular fluid at inflammation loci, is sufficiently acidic to activate complement. The exact molecular mechanism of this activation is still unclear, but possible cross talk between the contact system and complement may exist at low pH with subsequent complement activation. The current article reviews the published data on the effect of pH on the contact system and complement activity, the nature of the pH sensor molecules, and the clinical implications of these effects. Of particular interest is chronic kidney disease (CKD) accompanied by metabolic acidosis, in which therapeutic alkalinisation of urine has been shown significantly to reduce tubular complement activation products, an effect which may have important implications for slowing progression of CKD.